The effect of vacuum on the drying kinetics and mathematical modelling of blueberries - Kipcak, Ekin (YILDIZ TECHNICAL UNIV, 2024)
Blueberry is a small fruit, which has a very high amount of antioxidant substances. It is consumed either in fresh or dried form. In this study, the effect of vacuum on the oven thin-layer drying of blueberries was investigated. The kinetic parameters of effective moisture diffusivity ( D (eff) ) and activation energy (Ea) values were calculated. Moreover, the drying curves were modelled with the most known mathematical modelling equations given in the literature. For oven and vacuum oven drying, the drying temperatures were selected as 60, 70 and 80 degrees C. The drying times were seen to decrease by increasing the drying temperature and with the effect of vacuum. The highest drying time was observed as 420 minutes in oven drying at 60 degrees C. The effect of vacuum decreased this drying time to 240 minutes. D (eff) values were calculated to elucidate the underlying mass transfer mechanisms by using Fick's 2 nd law, which were found to be between 1.14-2.83x10(-9) m(2)/s (2) /s for oven drying and increased to 2.54-4.33x10(-9) m(2)/s (2) /s by the addition of vacuum. Likewise, activation energy was increased from 25.93 to 43.98 kJ/mol by vacuum addition. Twelve mathematical models were applied to the drying curve data and among them, Alibas model for both oven drying and vacuum-assisted oven drying gave the coefficient of determination (R-2) values that were higher than 0.997. As a result, the vacuum addition was seen to yield lower drying times and higher kinetic parameters for the oven drying of blueberries.
Keywords: Activation Energy; Blueberry; Drying; Effective Moisture Diffusivity; Oven; Vacuum; ENERGY-CONSUMPTION; MICROWAVE; TEMPERATURE; Engineering